Performance of young calves supplemented with vitamins C and E and beta-carotene - R.H. Greenwood; J.L Morrill; J.R. Schwenke (Kansas Agricultural Experiment Station Research Reports, 1996)
Newborn Holstein calves were used to investigate responses to supplemental antioxidants provided in daily milk allotments. Treated calves assigned to receive daily 100 IU of d-α tocopherol (vitamin E), 5 mg of beta-carotene, and 500 mg of ascorbic acid (vitamin C) in a 5-ml carrier. Control calves received the carrier alone. Additional vitamins C and E and beta carotene did not affect weaning age, weekly or total body weight gain, or dry feed intake. Supplementation of these antioxidants affected bull and heifer calves scour scores differently at different birth weights. Antioxidant supplementation increased the severity of scours during the first week for bull and heifer calves and the second week for bull calves but decreased the severity for heifer calves during the second week.; Dairy Day, 1996, Kansas State University, Manhattan, KS, 1996;
Keywords: Dairy Day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-115-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 771; Antioxidants; Calf Performance; Scours scores